Sistem Pendukung Keputusan dalam Menentukan Strategi Manajemen Resiko UMKM Berbasis Web Dengan Metode Certainty Factor - Saiful, Muhammad; Samsu, L M; Editri Sutriandi, Aswian (Infotek: Jurnal Informatika dan Teknologi, 2024)
Risk management plays a crucial role in securing the sustainability and growth of Micro, Small, and Medium Enterprises (MSMEs). Amidst the ever-changing complexity of the business environment, an efficient approach is needed to identify, analyze, and address the risks faced by MSMEs. This research aims to investigate the implementation of web-based Decision Support Systems (DSS) using the Certainty Factor method as a risk management strategy for MSMEs. The risk data obtained will be used to build a knowledge base in the form of a decision support system integrated into a web application. The implementation of web-based DSS provides wide accessibility advantages for MSMEs in managing risks. By utilizing the web application, MSME stakeholders can identify relevant risks in their field of business, analyze the impact and probability of each risk, and receive appropriate action recommendations. The results of this research indicate that the implementation of web-based DSS using the Certainty Factor method is effective in supporting MSMEs in risk management. MSMEs that utilize this application can make more informed and timely risk decisions, reducing potential losses. Therefore, it is hoped that this research can make a significant contribution to enhancing the resilience of MSMEs in facing the complexities of the business environment.